STUDENT OPTIMAL SIMULATION (SOS) : FIRST AID EDUCATION IN CHOKING CASES AT SCHOOL INDONESIA SINGAPORE (SIS) - Levina, Intan; Huda, Mochammad Maftuchul; Setyorini, Dwi; Azizah, Siti Nur (CV. Alina, 2024)
First aid in child choking is an essential skill that everyone should have, especially children who are a vulnerable group to choking events that can be fatal. This study aims to analyze the educational strategies of grade 2 children at Sekolah Indonesia Singapura (SIS) in dealing with choking situations. The service method includes delivering material through interactive lectures, practical demonstrations, and role plays. The intervention results showed increased children's knowledge and skills in recognizing signs of choking and appropriate first aid steps. This condition reinforces the importance of early first aid education in reducing the risk of accidents in children. These skills can also be applied in the surrounding environment, including at home and in public places. Children's education strategies effectively improve children's safety in dealing with choking events.